PENGARUH FAKTOR BUDAYA TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH JASA PERBANKAN SYARIAH (STUDI PADA BANK SYARIAH INDONESIA (BSI) KANTOR CABANG PEMBANTU GRONG-GRONG) - Ibrahim, Ibrahim (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
The diversity of products and services offered by banking institutions provides ample opportunities for consumers to choose banking institutions that suit their needs. Consumer decisions in using or making purchases are influenced by cultural factors. By always paying attention to these factors, consumers will decide to use the company's products or services. The problem formulation in this research is whether cultural factors influence customer decisions in choosing BSI KCP Grong-Grong, using quantitative methods. The number of samples involved in this research was 100 customers using the purposive sampling method. The research results show that cultural factors have a significant influence on customers' decisions in choosing BSI KCP Grong-Grong. The lower the cultural factor, the lower the customer's decision to choose BSI KCP Grong-Grong, and vice versa, if the cultural factor is higher, the higher the customer's decision to choose BSI KCP Grong-Grong.